1984
DOI: 10.1037/0096-1523.10.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Expectancy and dual-task interference.

Abstract: This research deals with the relationship between expectancy and attention. In two experiments, expectancy concerning the modality of a probe stimulus was manipulated. In Experiment 1, the frequencies of probes in auditory and visual modalities were varied. In Experiment 2, a cue prior to each trial indicated the relative probabilities of the two types of probes. In both experiments, expectancy effects were observed in a single-task condition during which the subject's only task was to respond to the probes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…A single key was pressed irrespective of target location. The advantage of the cued over the uncued location in RT has been confirmed many times (Hughes & Zimba, 1985;Jonides, 1981;Lansman, Farr, & Hunt, 1984;Posner, 1980) and has often been attributed to the covert shift of attention to the cued location.…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…A single key was pressed irrespective of target location. The advantage of the cued over the uncued location in RT has been confirmed many times (Hughes & Zimba, 1985;Jonides, 1981;Lansman, Farr, & Hunt, 1984;Posner, 1980) and has often been attributed to the covert shift of attention to the cued location.…”
Section: Methodsmentioning
confidence: 80%
“…There is already some evidence that dual tasks influence the ability to shift attention toward a cue. In one study researchers found that cuing the modality of a probe (visual vs. auditory) produced significantly faster RTs for the cued modality (Lansman et al, 1984), but these cuing effects were reduced or eliminated when perfonned during a dual task. In another study, when counting backward, the subjects were affected less by spatial cues during a dual task than during a spatial orienting task alone (Posner, Cohen, Choate, Hockey, & Maylor, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…Attention is often discussed as if it were a single, unitary mechanism. Recent behavioral research indicates that different methods of manipulating attention may tap different mechanisms (e.g., Briand & Klein, 1987; Lansman, Farr, & Hunt, 1984; Miller, 1988; Muller & Rabbitt, 1989; Nakayama & Mackeben, 1989). Indeed, physiological research indicates that there are perhaps dozens of neural structures that may mediate attention (Colby, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…The more of what we see and hear that is dominated by the virtual world, the more attention that should be focused there, and vice versa. ______________________________________________________________________________________ In this experiment, we constructed a divided attention task similar to those used in traditional dual-task paradigm experiments [5][6][7][8]. We designed a virtual world experience with a content rich storyline that could be used in a question and answer session after each trial.…”
Section: Approachmentioning
confidence: 99%